2015
DOI: 10.2147/dddt.s92777
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect and mechanism of honokiol on type 2 diabetic mice

Abstract: BackgroundHonokiol is one of the main bioactive constituents of the traditional Chinese herbal drug Magnolia bark (Cortex Magnoliae officinalis, Hou Po). The aim of this study was to probe its anti-type 2 diabetes mellitus effects and the underlying mechanism.MethodsType 2 diabetic mouse model was established by intraperitoneally injecting with streptozotocin. Fasting blood glucose, body weight, and lipid profile were measured. The subcutaneous adipose tissue, skeletal muscle, and liver were isolated as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Fortunately, recent research has shown that new dosage forms of honokiol were developed to improve its solubility and bioavailability without toxic side effects, making it better for clinical use (35,36). It was reported that mice were orally administered 200 mg/kg honokiol for 8 weeks without any toxicity and with good tolerance and high median lethal dose safety (25). In addition, intravenous administration of 20 to 80 mg/kg in rats showed no significant difference in serum biochemical parameters or histopathological changes in the rats (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, recent research has shown that new dosage forms of honokiol were developed to improve its solubility and bioavailability without toxic side effects, making it better for clinical use (35,36). It was reported that mice were orally administered 200 mg/kg honokiol for 8 weeks without any toxicity and with good tolerance and high median lethal dose safety (25). In addition, intravenous administration of 20 to 80 mg/kg in rats showed no significant difference in serum biochemical parameters or histopathological changes in the rats (37).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our study found a natural compound, honokiol [3=,5-di-(2-propenyl)-1,1=biphenyl-2,4=-diol], which is mainly derived from the dry skin and the root bark and branch bark of Magnolia officinalis, to be an effective MCR-1 inhibitor. Honokiol performs various pharmacological functions, including anti-inflammatory, antiulcer, antioxidation, anti-aging, antitumor, and cholesterol-lowering activities, and it displays significant protection of the central nervous system (22)(23)(24)(25)(26). As yet, there has been no report of honokiol as an inhibitor of resistant enzymes.…”
mentioning
confidence: 99%
“…Honokiol, a phenolic compound, has been isolated from the bark of the Magnolia officinalis tree. It has been used in traditional Chinese medicine due to its potent properties, which include anti-hyperglycemic [ 12 ], anti-depressant [ 13 ], anti-tumor [ 14 ], and anti-inflammatory abilities [ 15 ]. Previous work from our lab has shown that honokiol can inhibit adhesion, transition from yeast to hypha, and biofilm formation in C .…”
Section: Introductionmentioning
confidence: 99%
“…Honokiol, a neolignan isolated from the oriental medicine plant Magnolia officinalis , is an interesting compound exhibiting various pharmacological activities in preclinical experimental models [ 10 14 ]. Honokiol molecule contains two phenolic groups which can exhibit antioxidant properties similar to vitamin E or polyphenols.…”
Section: Introductionmentioning
confidence: 99%